Flu vaccination coverage in a large Italian teaching hospital: the example of the leaders. (13th November 2019) - Pumpo, M Di; Barbara, A; La Milia, D I; Tamburrano, A; Vallone, D; Gentili, A; Cavalieri, S; Viora, C; Berloco, F; Laurenti, P
Abstract: : Annual flu vaccination among healthcare workers (HCWs) is recommended to prevent influenza and to avoid its transmission especially to frail patients. In our teaching hospital, flu vaccination rate among HCWs has been growing during last 3 years. The aim of this study was therefore to describe the flu vaccination coverage across the past 3 years and to analyze which factors lead to such increase. We performed a cross-sectional study on all HCWs of Fondazione Policlinico Universitario "A. Gemelli" (FPG) hospital of Rome (Italy) to determine the flu vaccination coverage. Socio-demographic and occupational data were collected from hospital personnel records and included age, gender, previous flu vaccination, profession and workplace unit. On site vaccination plus academic detailing involving leaders have been the main strategies adopted in this last 3 years that have already proved to be effective in increasing vaccination coverage among HCWs. During the 2018-2019 season, we analyzed how the flu vaccination coverage among leaders (nurse coordinators and head physicians) could affect all HCWs coverage rate. Flu vaccination rate increased from 9.57% in the 2016-17 to 14.24% in the 2017-18 and to 22.38% in 2018-2019. A total of 4035 HCWs employed in the FPG were included in 2018-19. Concerning the role played by vaccination of leaders in increasing general vaccination coverage during the 2018-2019, the group of HCWs with a vaccinated leader showed a higher coverage rate (28.65%) than the group with a non-vaccinated leader (16.22%) (p < 0.0001). The results are preliminary. Flu vaccination coverage of HCWs in our hospital during the last 3 years has been increasingly higher. Vaccination of the leaders, in addition to previously implemented effective strategies, resulted to be a key factor in increasing flu vaccination coverage among all HCWs. Socio-demographic and occupational variables can significantly influence the coverage rate as well. Key messages: Annual flu vaccination among healthcare workers (HCWs) is recommended to prevent influenza and to avoid its transmission especially to frail patients. This study shows the growing flu vaccination coverage rate in our teaching hospital and the effectiveness of the example given by the vaccinated leaders in increasing the coverage among all HCWs.